BUNGA PINJAMAN DALAM PERSPEKTIF KEADILAN (Studi Kasus Bunga Pinjaman di KPRI Nusantara IAIN Walisongo) - Ajib, Ghufron (Economica: Jurnal Ekonomi Islam, 2013)
The subject matter of this study motivated several considerations. The first is that justice is the mainÂ  major Islamic mission, including social and economic justice. The opponent of justice, namely zhulm (injustice), according to the modernist isÂ  raison detre ofÂ  usury prohibition, and be decisive for usuryÂ  legal issues. Second, that since 1990 up to the present system of Shariah financial institutions more firmly and growing rapidly with the issuance of Law numberÂ  21, 2008 On Islamic Banking and the issuanceÂ  Minister of Cooperative Regulation 91, 2004 On Guidelines for the Implementation of Activities Cooperative Business Financial Services Shariah. While the savings and loan business unit in KPRI âNusantaraâ since its establishment, in 1973, untill now still running a conventional loan system. In this study, primary data, the loan system and the pattern of calculating interest on savings and loans unit KPRI Nusantara, collected using three methods: participant observation, and interviews with the management and documentat.By using the concept of social justice of John Rawls, the concept maqashid al-Sharia, and the concept of Islamic financial cooperative systems, researchers discuss the issue through three aspects of justice, namely the aspect of contract, the consistency aspect of interest, and justice aspects of cooperatives. Two discussion of this study conclude the absence of justice, namely the aspects of the contract and consistency aspects of interest. The final discussion concludes that there is justice, which is the aspect justice cooperatives.